Temporal characteristics and associated factors of discontinuation and outcomes after percutaneous coronary intervention - Xu, Haiyan; Zheng, Wanxiang; Tan, Jiangqin; Li, Min (Frontiers in Pharmacology, 2024)
Background: Medication adherence in patients after percutaneous coronary intervention (PCI) is suboptimal, and discontinuation is common. Information on the temporal characteristics and associated factors of discontinuation and outcomes after PCI is insufficient to improve medication adherence interventions. Methods: We conducted a single-center retrospective study of post-PCI patients by telephone survey and medical record extraction. Temporal characteristics and associated factors of discontinuation and outcomes were examined by survival curve analysis, Cox regression, or time-dependent Cox regression. Results: Discontinuation and majoradverse cardiovascular events (MACE) after PCI had similar temporal characteristics, with the highest incidence in the first year, followed by a decline. Temporary discontinuation was associated with pre-PCI medication non-adherence (HR 1.63; 95%